Physical Processes in Sea Fog Formation and Characteristics of Turbulent Air-Sea Fluxes at Socheongcho Ocean Research Station in the Yellow Sea - Yun, Junghee; Ha, Kyung-Ja (Frontiers in Marine Science, 2022)
The Yellow Sea is the most fog-prone region of the East Asian marginal seas. Since sea fog is caused due to complex interactions between atmospheric and oceanic environments, direct observations can help understand the physical processes involved in fogging over the oceans. Completed in 2014, the Socheongcho Ocean Research Station (S-ORS) plays a critical role in monitoring air-sea interactions over the Yellow Sea. This study aimed to evaluate the conditions favorable for fog generation and the physical processes underlying it using a suite of observations and turbulent heat flux data from S-ORS. First, we used the visibility data from S-ORS to quantify the frequency of sea fog over the Yellow Sea. From April to June 2016, sea-fog occurred 61 times, with a maximum duration of 135 h (approximately 5.6 days). Next, to understand the origin and characteristics of air mass associated with fog events, we classified the primary airflow paths in the region using a Hybrid Single-Particle Lagrangian Integrated Trajectory model. Among the four clusters identified from the cluster analysis, the third and fourth had distinct physical properties characteristic of cold and warm fog, respectively. The third cluster was characterized by relatively weak or negative heat advection and weak vertical mixing, while the fourth one featured strong positive heat transport and moisture convergence over the Yellow Sea. Finally, based on cluster analysis, we choose the representative cases related to these two clusters observed at S-ORS and compared the characteristics of turbulent air-sea fluxes associated with fog formations.